2022
DOI: 10.14482/sun.37.3.616.98
|View full text |Cite
|
Sign up to set email alerts
|

Estrés, ansiedad, depresión y apoyo familiar en universitarios mexicanos durante la pandemia de COVID-19

Abstract: Objetivo: Identificar los niveles de estrés, ansiedad y depresión presentes en los universitarios durante la pandemia en relación con el apoyo que brinda la familia. Materiales y Métodos: Se trata de un estudio de tipo cuantitativo con un diseño descriptivo, correlacional y transversal. La muestra (n=105), fueron estudiantes de la facultad de Enfermería de la Universidad Veracruzana; se obtuvo a través de un muestreo no-probabilístico a conveniencia. Los datos fueron recolectados a través de un instrumento dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In these social strata, the number of infections and deaths are higher and therefore cause a greater impact on the population. Regarding the perceived family functioning, a divergence is identified with what was obtained by Estrada (2010) (cited by Pérez, López and de León, 2022), United Nations Fund for Children Argentina (2020), United Nations Fund for Children Mexico (2020) and Pérez et al (2021) in their analysis of families during periods of confinement, in these a deterioration of family relationships was observed as a result of confinement or the increase in conflicts; while, the results obtained in the present investigation reveal that students perceive family relationships as moderately functional, however, in other contexts and taking into account the perception of family functioning from parents, it can be observed that they usually see the dynamics family as functional, where there is correct communication, cohesion and displays of affection, as mentioned by Vargas, Villafaña, Moysén and Eguiluz (2019) in their study on suicide, where then, the family is evidenced as a means of Extremely important social support in traumatic situations such as suicide attempts and health crises. Regarding the contrast between the groups of men and women, the data obtained show us that there are statistically significant differences for the anxiety and stress variables in these groups, which is also reflected in the studies carried out by Galindo et al (2020); González, Tejeda, Espinoza and Ontiveros (2020); Orellana and Orellana (2020), who indicate that the symptoms related to these variables are predominant in women, largely due to the overload of activities that this group usually has and the social expectations that are placed on them in terms of compliance with their gender role, which is why women tend to present more intense symptoms of anxiety and stress compared to men, who tend to have a mild expression of these symptoms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In these social strata, the number of infections and deaths are higher and therefore cause a greater impact on the population. Regarding the perceived family functioning, a divergence is identified with what was obtained by Estrada (2010) (cited by Pérez, López and de León, 2022), United Nations Fund for Children Argentina (2020), United Nations Fund for Children Mexico (2020) and Pérez et al (2021) in their analysis of families during periods of confinement, in these a deterioration of family relationships was observed as a result of confinement or the increase in conflicts; while, the results obtained in the present investigation reveal that students perceive family relationships as moderately functional, however, in other contexts and taking into account the perception of family functioning from parents, it can be observed that they usually see the dynamics family as functional, where there is correct communication, cohesion and displays of affection, as mentioned by Vargas, Villafaña, Moysén and Eguiluz (2019) in their study on suicide, where then, the family is evidenced as a means of Extremely important social support in traumatic situations such as suicide attempts and health crises. Regarding the contrast between the groups of men and women, the data obtained show us that there are statistically significant differences for the anxiety and stress variables in these groups, which is also reflected in the studies carried out by Galindo et al (2020); González, Tejeda, Espinoza and Ontiveros (2020); Orellana and Orellana (2020), who indicate that the symptoms related to these variables are predominant in women, largely due to the overload of activities that this group usually has and the social expectations that are placed on them in terms of compliance with their gender role, which is why women tend to present more intense symptoms of anxiety and stress compared to men, who tend to have a mild expression of these symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…However, in the same way, it can generate problems that destabilize the members. In Mexico, in a study carried out by Pérez et al (2021) on family support, depression, anxiety, and stress in university students during the COVID-19 pandemic we are currently experiencing, there are no significant correlations between these variables; however, the results show that students perceive little family support, since displays of affection and adaptability and autonomy skills within the family are seen as insufficient, and therefore they do not perceive the family as a support network; In addition, these individuals present mild symptoms when faced with the variables of depression, anxiety, and stress. In other crises, such as a suicide attempt, it is possible to analyze how family functioning is perceived in a System; In a study carried out by Vargas, Villafaña, Moysén, and Eguiluz (2019), from the perspective of the parents, it was found that, despite the situation experienced, they perceived the family environment as functional, standing out in aspects such as affective involvement, communication, and problem-solving; this even though children with suicidal incidence reported chaotic family dynamics; In this way, it is possible to observe that, although families may have a support function in crises and contingencies, they may also become risk factors for presenting conflicts or dysfunctional emotional symptoms.…”
Section: Family Functioning and Emotional Responses In Crisis Situationsmentioning
confidence: 99%
“…Sólo se encontró un estudio sobre el uso problemático de las TIC en adolescentes 5 y su relación con la salud. A pesar de que existen estudios que abordan la salud mental en estudiantes mexicanos durante la pandemia, se han enfocado únicamente en universitarios y no han abordado la comparación entre la situación previa a la pandemia y durante la misma 6,7,8,9 .…”
Section: Introductionunclassified
“…La salud mental es un tema cada vez más relevante en el campo académico, con un enfoque particular en la educación superior. El estrés, la ansiedad y la depresión se han consolidado como problemáticas recurrentes entre los estudiantes, y esto se atribuye en gran parte a la presión constante que enfrentan para mantenerse a la par de los elevados estándares académicos (6). Este escenario puede conllevar a la inestabilidad en la salud mental de los estudiantes, desencadenando una serie de consecuencias que repercuten en toda la comunidad estudiantil.…”
Section: Introductionunclassified